2020
DOI: 10.1177/0165025420914986
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Identity Scale (FIS): A multinational validation and measurement invariance study among emerging adults

Abstract: The transition from financial dependence on one’s parents to financial self-sufficiency is one of the most relevant transitions during emerging adulthood. It is important to have an instrument able to assess emerging adults’ financial capabilities and to detect its change over time. The current article aims to collect international evidence of the Financial Identity Scale (FIS) validity and reliability. Cross-sectional data collected from 2,501 emerging adults aged 18–25 and belonging to three different countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 43 publications
3
16
1
Order By: Relevance
“…In addition, the mediator role of the proximal outcomes was in most cases only assumed rather than empirically investigated (Gudmunson & Danes, 2011). More so, in recent years, researchers recognized that identity formation in the domain of personal finances, which is not addressed in FFS model (Gudmunson & Danes, 2011), is also an important part of financial capabilities and a potential mediator between parental financial socialization and emerging adults’ financial behaviors (Bosch, Serido, Card, Shim, & Barber, 2016; Shim, Serido, Bosch, & Tang, 2013; Sorgente, Lanz, Serido, & Shim, 2018).…”
Section: Financial Identitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the mediator role of the proximal outcomes was in most cases only assumed rather than empirically investigated (Gudmunson & Danes, 2011). More so, in recent years, researchers recognized that identity formation in the domain of personal finances, which is not addressed in FFS model (Gudmunson & Danes, 2011), is also an important part of financial capabilities and a potential mediator between parental financial socialization and emerging adults’ financial behaviors (Bosch, Serido, Card, Shim, & Barber, 2016; Shim, Serido, Bosch, & Tang, 2013; Sorgente, Lanz, Serido, & Shim, 2018).…”
Section: Financial Identitymentioning
confidence: 99%
“…Building upon a classical identity status model (Marcia, 1966), researchers suggested that the two fundamental processes of identity formation, that is, exploration (active search for information) and commitment (selecting what fits one’s worldviews best), may very well explain the development of an identity related to financial values and behaviors. In line with the classical identity status model, four statuses of financial identity were defined (Bosch et al, 2016; Shim et al, 2013; Sorgente et al, 2018). Achieved reflects one’s commitment to a financial management style that was made after exploring a range of alternatives in managing money.…”
Section: Financial Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…The construct and a measure of financial identity status were introduced (Shim et al, 2013) to study emerging adults’ distinct manner of approaching and managing personal finances. Subsequent studies of financial identity status led to important insights into the formation of positive financial habits and how financial identity contributes to financial well-being; however, very few studies used a longitudinal approach to study these associations (Bosch et al, 2016; Shim et al, 2013; Sorgente et al, 2020; Vosylis & Erentaitė, 2020). Thus, the directionality of effects is in question.…”
mentioning
confidence: 99%
“…Stemming from Marcia’s paradigm, similar scales were also constructed to afford insights into developmental aspects of specific identity domains, for example, financial (e.g., Bosch et al., 2016; Sorgente et al., 2020) and religious (Stojković et al, 2020). These scales demonstrated validity and relevance in studying identity-related outcomes.…”
Section: Civic Identity and Its Developmentmentioning
confidence: 99%